2010
DOI: 10.1063/1.3428774
|View full text |Cite
|
Sign up to set email alerts
|

Flexural deformation in a compositionally stepped ferrite and magnetoelectric effects in a composite with piezoelectrics

Abstract: The nature of strain mediated magnetoelectric (ME) coupling is investigated in laminates of lead zirconate titanate (PZT) and compositionally stepped ferrite with grading of piezomagnetic coefficient. ME effects that could only be attributed to grading related bending strain are observed in a trilayer of ferrite and oppositely poled PZT. It is shown that in a bilayer, grading induced flexural strain counteracts bending moment due to structural asymmetry and enhances ME coupling by a factor of 2. A zero-bias fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 12 publications
2
63
0
3
Order By: Relevance
“…High ␣ E of trilayer and zero ␣ ER was related to structural symmetry which reduces in-plane strain and maximizes the out-of-plane strain. 8 The peak position in this curve corresponds with the maximum in gradient of the magnetostriction versus magnetic dc bias curve. Please note the electrical connection in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High ␣ E of trilayer and zero ␣ ER was related to structural symmetry which reduces in-plane strain and maximizes the out-of-plane strain. 8 The peak position in this curve corresponds with the maximum in gradient of the magnetostriction versus magnetic dc bias curve. Please note the electrical connection in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reported ME composites in literature require magnetic dc bias to invoke piezomagnetic response and only recently, Mandal et al demonstrated selfbiased laminate composites where ME response at zero field was correlated with presence of flexural deformation in a compositionally graded structure. [8][9][10] However, this method of generating self-bias is dependent upon the composition grading and requires special synthesis process. Our research has been focused on finding a methodology where we can achieve self-biasing by just changing the electrical connections with regular laminate composites.…”
Section: Introductionmentioning
confidence: 99%
“…The Ni provided a field to bias the ME sensor. 10,11 The measuring system consisted of a set of Helmholtz coils, powered by an Agilent 33220 A signal generator that was used to apply a sinusoidal, time varying field H s along the longitudinal axis of the sensor. In these experiments, we did not employ any flux concentrators.…”
Section: Methodsmentioning
confidence: 99%
“…Note that if the laminate had perfect structural and compositional symmetry, the voltage generation would be completely zero under longitudinal magnetic field due to the 180 voltage phase difference between top and bottom KNNs. 8 Figures 2(b) and 2(c) illustrate the DME and CME response of the laminate in the same frequency range under applied H bias ¼ 0 and 100 Oe. Under zero H bias condition, both a DME and a CME values exhibited maximum enhancement at 21 kHz and much weaker response at 47 kHz.…”
Section: Fig 2 (Color Online) (A)mentioning
confidence: 99%
“…However, recent studies have revealed that by employing heterogeneous ferromagnetic structure, a large a DME value can be obtained in the absence of H bias , so called self-biased DME effect. [8][9][10] The selfbiased DME effect was observed when the laminates were operated in bending mode and consisted of dissimilar or graded magnetic materials that resulted in built-in magnetic bias. The discovery of self-biased DME effect is encouraging for applications such as self-biased magnetic field sensor.…”
mentioning
confidence: 99%